Chromium (III) Produces Distinct Type of Cell Death in Cultured Cells - Emil Rudolf; Miroslav Červinka (Acta Medica, 2003)
Chromium acetate hydroxide is a chemical form of trivalent chromium (Cr III) originating from industrial processes. Although considered relatively nontoxic, upon longer treatment intervals it may cause irreversible cellular damage culminating in cell death. In our present work we have attempted to analyze some of the mechanisms whereby this chemical inflicts damage while focusing on the final observed endpoints. We report that 1 mM chromium acetate hydroxide is during weeks lasting treatment capable of injuring the plasma membrane of Hep-2 cells, which in turn becomes permeable to Cr (III) ions. Analyses of several markers of cellular damage; i.e. mitochondrial activity, nuclear integrity and oxidative stress have shown that tested compound interacts directly with subcellular organelles and upon tested concentration and time induces distinct type of cell death bearing features of apoptosis and necrosis.